Essays on executive stock options in Malaysia (IR) - Zuriadah Ismail (2014)
This thesis examines four questions in the field of executive stock option plans: the legal framework governing their use in Malaysia, their effects on firm performance, managerial turnover and the tax effects. The research presented in this thesis extends the literature on stock options in these directions. Owing to the dearth of studies that have examined the issue of stock option plans, as well as the uniqueness of the Malaysian corporate environment which is dominated by family controlled firms. Using standard event study methodology, in the short-term, the results indicate a negative share price before announcement and a slight positive effect following the announcement. The announcement, however, does not carry any surprise to the market and this seemingly confirms that early information releases before official announcement could be ruled out. Over the long-term, the results indicate that stock option plans have no significant effect on the performance of Malaysian firms, suggesting that executive stock option plans do not entirely improve the value of Malaysian firms. Further examinations over the incentive of stock option plans indicate reductions in top executive turnover in Malaysia listed firms. The effects of executive stock option plans in mitigating unplanned turnover at the executive levels take into account the mediating control variables at firm level such as ownership structure, corporate governance, firm characteristics and level of pay. The consequences of executive turnover are focused on firm performance. Using accounting and market performance measures, the result indicates that poor firm performance lead to high executive turnover. However, the study documents weak support for performance measures in the evaluation of executive turnover. The thesis also examine other factors that are likely to influence executive turnover, of which the empirical results indicate that managerial ownership, board attributes and firm size do not lead to high executive turnover. However, mix payments are found to be influenced the management turnover. This thesis also exam ines and attempts to understand the effect of stock option and tax benefits between corporate taxpayer and personal taxpayer, which is found to be ambiguous. Although previous empirical results indicate that taxpayers may extend their tax liability usually for three to five following the grant date, but it would seem that Malaysian stock option programs do not produce any tax preferential treatments in our sample. This is due to limitation in the Malaysia tax policy which makes no allowance for expenses-related to stock options. This appears that Malaysia taxation rules do not affect tax benefits. However when the data for tax groups were decomposed according to information disclosed in annual reports for executive and the firm, the result suggests that executive stock options are responsive to changes in personal income tax rate. For firm, awarding stock option is perhaps driven by a psychological contract between executives, rather than tax incentives, which suggest that cash payment salary and bonus are significant component for executive payments in Malaysia.